2003
DOI: 10.1177/070674370304800907
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour in Children with Language Development Disorders

Abstract: In general, our results agree with several studies that report that children with speech and language disorders are at special risk for developing behavioural problems. Neurodevelopmental immaturity may be one factor underlying both the disorder in language development and the behavioural problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 39 publications
3
37
0
3
Order By: Relevance
“…We found that, similar to international studies, Brazilian children with SLI had more behavior problems and showed less social competence than the general population (Macharey and von Suchodoletz 2008;St Clair et al 2011;Van Agt et al 2011;van Daal et al 2007). The percentage of children in this sample classified as "at risk of" total behavior problems (50 %) was higher than rates reported in previous studies with younger children (van Daal et al 2007;Willinger et al 2003), but lower than those from German language-impaired children from the same age range (Noterdaeme and Amorosa 1999). Behavior problems included both internalizing and externalizing difficulties, but were more evident for the former.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that, similar to international studies, Brazilian children with SLI had more behavior problems and showed less social competence than the general population (Macharey and von Suchodoletz 2008;St Clair et al 2011;Van Agt et al 2011;van Daal et al 2007). The percentage of children in this sample classified as "at risk of" total behavior problems (50 %) was higher than rates reported in previous studies with younger children (van Daal et al 2007;Willinger et al 2003), but lower than those from German language-impaired children from the same age range (Noterdaeme and Amorosa 1999). Behavior problems included both internalizing and externalizing difficulties, but were more evident for the former.…”
Section: Discussionsupporting
confidence: 82%
“…However, because no consensus has been reached on the prevalence of behavioral and social problems among children with SLI, we did not raise specific predictions, but rather expected to find a percentage ranging from approximately 40 % (Beitchman et al 1986;Willinger et al 2003;van Daal et al 2007) to 80 % (Noterdaeme and Amorosa 1999).…”
Section: Introductionmentioning
confidence: 85%
“…Campbell et al (2003) are more specific when suggesting that if 75 per cent or less of what a child is trying to express can be understood that would be indicative of a language difficulty. This is a thought-provoking statement as it is not clear how the child is trying to express; many children use gestures, facial expressions and body language to make their wants and needs clear, however, and are unable to verbally make their wants and needs clear (Iverson et al 1994;GoldinMeadow 2000;Bates and Dick 2002;Palaiologou, 2010 (Campbell et al 2003;Willinger et al 2003;Hauner et al, 2005).…”
Section: The Complexities Of Identifying Language Difficultiesmentioning
confidence: 99%
“…As indicated by Bishop & Edmundson (1987), the longer these disorders persist, the greater the possibility of continued difficulty in these and related areas. For example, studies have demonstrated that children with these disorders have a greater possibility of reading difficulty (Schuele, 2004), mental health issues (e.g., depression, anxiety; Beitchman et al, 2001;Conti-Ramsden, & Botting, 2008;Sundheim & Voeller, 2004), and behavioral problems (Beitchman et al, 2001;Willinger et al, 2003) when compared to children without a history of language disorders. These challenges in turn lead to difficulties with school (Schuele, 2004) and in social relationships, especially bullying or exclusion by peers (Hughes, 2014;Snowling, Bishop, Stothard, Chipchase, & Kaplan, 2006).…”
Section: Introductionmentioning
confidence: 99%